2021
DOI: 10.1038/s41598-021-00852-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the diagnostic performance of five commercial COVID-19 qRT PCR kits used in India

Abstract: To meet the unprecedented requirement of diagnostic testing for SARS-CoV-2, a large number of diagnostic kits were authorized by concerned authorities for diagnostic use within a short period of time during the initial phases of the ongoing pandemic. We undertook this study to evaluate the inter-test agreement and other key operational features of 5 such commercial kits that have been extensively used in India for routine diagnostic testing for COVID-19. The five commercial kits were evaluated, using a panel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…For example, the Gerbion GmbH & Co. diagnostics kit showed a detection efficiency of 49%, while the kit from SolGent Co., Ltd. manufacturer showed a detection efficiency of 92% in SARS-CoV-2 detection [ 6 ]. On the other hand, a study in India showed differences of up to 21% between the RT-qPCR kits used for the COVID-19 diagnosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Gerbion GmbH & Co. diagnostics kit showed a detection efficiency of 49%, while the kit from SolGent Co., Ltd. manufacturer showed a detection efficiency of 92% in SARS-CoV-2 detection [ 6 ]. On the other hand, a study in India showed differences of up to 21% between the RT-qPCR kits used for the COVID-19 diagnosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity and specificity are reported as a mean (95% confidence limits). The forest plot represents the estimated sensitivity and specificity (black squares) and their 95% confidence limits (horizontal black line) [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Sensitivity and specificity are reported as a mean (95% confidence limits).…”
Section: Discussionmentioning
confidence: 99%
“…Positive Likelihood ratio, Negative likelihood ratio, and Diagnostic Odds ratio are reported with a mean (95% confidence limits). The Forest plot depicts the estimated sensitivity and specificity (black squares) and its 95% confidence limits (horizontal black line) [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. For all outcomes, present, for each study: (a) summary statistics for each group (where appropriate) and (b) an effect estimate and its precision (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of the single-tube multiplex assays for SARS-CoV-2 proved advantageous with respect to time and labor. However, each commercial kit differed in its targets and sensitivities ( 76 78 ). Therefore, having multiple confirmatory genes served to compensate for the sensitivity and specificity of its targets.…”
Section: Impact Of Sars-cov-2 Variants On Diagnostics/detectionmentioning
confidence: 99%